THE CURRENT STATE AND PROBLEMS OF MULTIMODAL RADIATION DIAGNOSIS OF PNEUMONIA WITH THE ASSOCIATION OF CORONAVIRUS INFECTION - Jonibekov Jasurbek Jonibekovich (Researchparks Publishing, 2022)
Coronavirus infection (COVID-19) is an acute infectious disease caused by a new strain of SARS CoV—2 coronavirus with an aerosol-drip and contact-household transmission mechanism. Pathogenetically COVID-19 is characterized by viremia, local and systemic immuno-inflammatory process, hyperactivity of the coagulation cascade, endotheliopathy, hypoxia, which leads to the development of micro- and macrothrombosis; it proceeds from asymptomatic to clinically pronounced forms with intoxication, fever, vascular endothelium damage, lungs, heart, kidneys, gastrointestinal tract, central and peripheral nervous systems with the risk of complications (ODN, ARDS, PE, sepsis, shock, SPON). The main target of SARS CoV-2 is the lungs. In pathogenesis, 2 mechanisms should be distinguished that mutually burden each other and can lead to the development of ARDS (pathomorphologically diffuse alveolar damage): direct viral damage of alveocytes with the development of immuno-inflammatory syndrome; development of micro- and macrothrombosis of pulmonary vessels and obstructive thromboinflammatory syndrome [1.3.5.7.9].